32 Neuroendocrine Carcinoma of the Breast: An Underdiagnosed Neoplasm With Enhanced Metastatic Potential. (11th January 2018) - Alattia, Lubna; Knowles, Kurt; Shi, Mingxia; Georgescu, Maria-Magdalena
Abstract: Background: Primary neuroendocrine carcinoma of the breast (NECB) is a rare entity of breast cancer; it shows a neuroendocrine differentiation in at least 50% of tumor cells with positive immunoreactivity to neuroendocrine markers. Clinical features and morphology are not always enough to enable distinction of NECB from other subtypes of breast cancer. Case Presentation: We report three patients who presented with primary breast masses and subsequent skull and spinal masses. The patient ages were 62, 61 and 44 years old, and the metastatic mass sizes were 4.3, 4, and 2 cm, respectively. The histopathologic analysis showed metastatic breast carcinoma to the spine in the two older patients and a benign skull vascular lesion in the younger patient. Results: The first patient was diagnosed with thoracic spinal cord metastatic breast cancer as the first manifestation of her disease. Subsequent breast lumpectomy revealed a high-grade invasive ductal carcinoma. The second patient had an estrogen receptor (ER)-positive breast no special type (ductal) carcinoma refractory to conventional therapy for four years before developing a spinal mass. This mass showed focal rosette formation and investigation revealed positivity for neuroendocrine markers. This new diagnosis of neuroendocrine carcinoma prompted reanalysis with neuroendocrine markers of the first patient's tumors, as well as of that from a third patient, who presented with a breast mass and a skull lesion. Although the skull lesion was not a metastasis, all of these patients' ER-positive breast carcinomas were confirmed to be neuroendocrine breast tumors. Conclusion: Increased awareness of the existence of this highly metastatic breast tumor entity that may be resistant to conventional therapy will reduce its underdiagnosis and allow better clinical management of this disease.